Kegiatan Insentif dan Penyelamatan Sapi dan Kerbau Betina Produktif di Sumatera Barat tahun 2011-2012 - F. Madarisa; Edwardi Edwardi; A. Arman (Universitas Andalas, 2013)
A survey has been conducted to observe the activity of delivering budget scheme to livestock farmers groups in West Sumatra 2011-2012. Its objective was to prevent both productive cow and buffalo from slaughtering process. Within a system approach, at least two activities have been launched to deal with such prevention program; (1) incentive budget as a driving force to keep livestock living at farmers groups and (2) getting back productive cow and buffalo from intended marketing chains. A designed questioner has been offered to 146 farmers groups to collect primary data. Secondary data was collected from related publications. The result showed that incentive was more effective and efficient compared to the get back productive cow. Thus, it is recommended that incentive budget should be continued with a social business approach in its market system. A number of activities could be followed to achieve such goals; (1) farmer groups activity as a main basis for incentive program; (2) making sure that groups could finalize the activity at the earlier process to keep farmers motivation high; (3) increasing both budget allocation and number of target recipient to the incentive activity.